An Approach for Integration of User Requirement and Anthropometry Data in The Process Design of Reactor Main Control Room - Setiawan, Muksin Aji; Santoso, Sigit; Suryono, Tulis Jojok; Kiswanta, Kiswanta; Purwaningsih, Anik; Maerani, Restu; Pamungkas, Adhika Enggar; Atmoko, Dian Fitri; Dwiardhika, Dhanu (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2023)
The construction of a Nuclear Power Plant (NPP) using Small Modular Reactor (SMR) technology is an interesting scheme to support Net-Zero Carbon Emission. The SMR design is an advanced generation reactor with high safety and utilization features, especially the electricity needed and industry. Its modular size can also be applied to remote areas with lower construction costs compared to other types of power plants. Considering the geographical location and territory of Indonesia which is an archipelagic country, this type of reactor is suitable for application in Indonesia. To ensure safety and increase mastery of technology, it is necessary to create a simulator to support this program. Nonetheless, specific regulations govern human-machine interactions (HMI) which is covering the nuclear reactor simulators in Indonesia is not yet available. The research carried out is a review of the regulations that have been implemented in other countries, then provides a choice of operator condition designs, which are adjusted to the average size of Indonesian by considering anthropometric aspects and ergonomic aspects.